HUBUNGAN PENCAHAYAAN RUANGAN DENGAN KELUHAN KELELAHAN MATA PADA PEKERJA BATIK TULIS DIDESA TRUSMI KULON PLERED KABUPATEN CIREBON - Nona Yeye; Mitha Erlisya Puspandhani; Sri Maryati (Jurnal Kesehatan Mahardika, 2018)
Background:Room lighting is the lighting that allows a person to lokk at work, see the work carefully, fast, clear and others, room lighting that is not standard can cause various health problems one of them is complaints of eyestrain. Based on preliminary study 11 of 20 batik workers experienced fatigue with eye complaints of sore eyes, dry eyes, and others. Purpose:The puspose of this study to determine the relationship of room lighting with complaints of eye fatigue on batik workers in the Village Ttrusmi Kulon Plered District Cirebon. Method:Type of descriptive correlation research with cross sectional study design.This research population of batik workers as much as 300 people. Sample was taken stratified random sampling as many 75 batik worker in 4 home industries. The instruments used in this study were the observation of room lighting and the eyestrain complaint questionnaire. Univariate data analysis with percentage and bivariate analysis with chi-square test. Result:The results showed from 75 workers in 4 home industries in the village of kulon, 34 workers experienced complaint of eye fatigue with a percentage of (45,3%), obtained 52% of respondents who got room lighting according to standards, the results of chi-square test of 0,000 that there is a relationship room lighting with complaints of eye fatigue on batik workers (p value 0,000 < 0,05). Conclusion:It is expected that the manager of batik to improve room lighting in order to increase the productivity of batik workers.